Evaluating the Use of Hot Potatoes in Learning Academic Word List - Zuraina, Ali (Science Publishing Corporation, 2018)
Technology has emerged as a powerful platform to assist learners in their learning. Moreover, a key aspect of learning using technology is its ability to reach audiences at anytime and anywhere. In the current study, Hot Potatoes is used to identify whether or not they are able to learn Academic Word List (AWL) in five (5) exercises namely JMix, JCloze, JCross, JMix and JMatch. Fifty-three words were selected for the purpose of testing their knowledge of the academic vocabulary. Online questionnaire was later administered to the students to examine the relationship between the effectiveness of using Hot Potatoes and its usefulness in learning 53 vocabulary in various forms of quizzes. Results from the study show that there are positive correlations between the two variables with high levels of effectiveness of using Hot Potatoes and its usefulness in learning vocabulary. In terms of effectiveness, the students who answer the survey believe that Hot Potatoes provides direct feedback by remarking students of their answers to be correct or wrong. Meanwhile, the platform is identified to be useful by its users due to its appropriate format of quizzes for cross-word puzzle, matching, fill-in the blanks, jumbled sentences, cloze text and multiple-choice questions. These format of exercises reinforce the learning of vocabulary. The contribution of this study, therefore, has been to confirm that developers who are teacher-researchers may not have to have programming knowledge in preparing online quizzes. Instead, with the use Hot Potatoes, interactive Web exercises can be developed by those who do not have such background.